PENGEMBANGAN LKPD BERBASIS PROYEK PENGOLAHAN LIMBAH KULIT NANAS UNTUK MELATIHKAN CREATIVE THINKING SKILLS DAN SELF-REGULATED LEARNING - Arifia, Amanda Fajar; Herlina, Kartini; Viyanti , Viyanti (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2025)
This study aims to develop a valid and practical project-based learner worksheet to train creative thinking skills and self-regulated learning on alternative energy material. This type of research is Design and Development Research (DDR) adapted from Richey & Klien (2007) using validity test consisting of empiric validation and expert validation, as well as practicality test consisting of readability test, teacher perception test, and learner response test, the effectiveness test consists of the results of the analysis of trained creative thinking skills and self-regulated learning in small groups. The results of the empiric validation test are seen based on the success of the biobattery product turning on the LED in a particular circuit. On the results of the expert validation test, obtained an average score from the three experts of 3.24, with the average score on the media and design aspects obtained at 3.32 with very valid category, and the material and construct aspects obtained at 3.15 with a valid category. The results of the practicality test obtained an average score for the readability test of 83.8% with a very practical category, the teacher perception test of 87.3% with a very good category, and the learner response test of 84.7% with a very good category, obtained an average practicality test score of 85.3% with a very practical category. The effectiveness test was seen based on the results of the analysis of trained creative thinking skills obtained the results of 81% and the analysis of trained self-regulated skills.